2022
DOI: 10.1093/scipol/scac067
|View full text |Cite
|
Sign up to set email alerts
|

Guidance on research integrity provided by pan-European discipline-specific learned societies: A scoping review

Abstract: There is little research on the content of research integrity (RI)–related guidance provided by pan-European discipline-specific learned societies, or how this guidance compares with recommendations made in the European Code of Conduct for Research Integrity (ALLEA code). Therefore, we aimed to (1) assess the availability of RI guidance from these learned societies, (2) compare learned societies’ guidance with the ALLEA code, and (3) explore similarities and differences in guidance between learned societies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Research Integrity (RI) is high on the agenda of both institutions and science policy (ALLEA, 2017 ; ENRIO, 2019 ; Evroux, 2022 ; Hastings et al, 2022 ; WCRI statements, 2010 , 2013 ). The European Union as well as national ministries of science have launched ambitious initiatives to combat research misconduct and breaches of RI.…”
Section: Introductionmentioning
confidence: 99%
“…Research Integrity (RI) is high on the agenda of both institutions and science policy (ALLEA, 2017 ; ENRIO, 2019 ; Evroux, 2022 ; Hastings et al, 2022 ; WCRI statements, 2010 , 2013 ). The European Union as well as national ministries of science have launched ambitious initiatives to combat research misconduct and breaches of RI.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature reviews have been found, showing in most cases the occurrence of serious and minor forms of misconduct in biomedical and behavioral research (Armond et al, 2021;Xie et al, 2021;Yi et al, 2019a) In another investigation, 58 IR documents from scientific societies of various scientific disciplines were analyzed. Less than a quarter provide IR guidelines, and there are significant differences between disciplines (Hastings et al, 2022). In addition to these reviews, the study of factors affecting the implementation of IR standards at the investigator, organizational, and science system levels (Roje et al, 2022) and the publication of integrity and research oversight (Muthanna & Alduais, 2021).…”
Section: Introductionmentioning
confidence: 99%